Navigating Uncertainty: Strengthening the Electric Vehicle Supply Chain Against Disruptions - Roy, Dipayan; Naresh Babu, E.M. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
There is a sea change in the usage of Electric Vehicles (EVs) that we have witnessed in the last decade but there are certain issues related to the Supply Chain of EVs. There are multiple issues associated with transportation sector such as greenhouse gas effects and pollution spread due to dependency on fossil fuels. There is significant evidence of growth in Electric vehicles in India from 2018 and a brisk change especially from 2021. But majority of the consumers are facing problems with respect to the Electric Vehicles Batteries. The present study highlights the perceptions and opinions of respondents who are associated with Electric Vehicle industry and majority of the respondents are feeling that environmentally friendly nature is the primary objective of purchasing EV and major limitation with EV is charging points. Most of the respondents are willing to purchase and suggest to purchase EVs in the next 5 years and majority of them are willing to pay premium also to safeguard the environment. According to many respondents, Recycling batteries also contribute to the sustainability. Hypotheses have been tested at 5% significance level to test the above findings.
Keywords: Electric Vehicles; EV Batteries; Fossil fuels; Greenhouse Gas; Global Mobility; Supply Chain